Estudo do papel da aspartil protease (pbsap) na virulência do fungo patogênico paracoccidioides brasiliensis - Castilho, Daniele Goncalves [UNIFESP] (2018)
Paracoccidioidomycosis (PCM) is the most prevalent deep mycosis in Latin America and is caused by fungi from the paracoccidioides genus. The development of the disease depends on factors associated with the host immune response and the infectious agent characteristics, especially virulence. Virulence factors are important fungal characteristics that support the development of disease. Aspartyl proteases (SAPS) are virulence factors in many human fungal pathogens that play an important role in the host invasion process. We report here that immunization with recombinant sap from paracoccidioides brasiliensis (rpbsap) imparted a protective effect in an experimental PCM model. The rpbsap-immunized mice had decreased fungal loads, and their lung parenchymas were notably preserved. Therapeutic treatment against model PCM using pepstatin a, an aspartyl protease inhibitor, decreased pulmonary injury and reduced fungal loads in the lung. Additionally, we observed that pepstatin a enhanced the fungicidal and phagocytic.